A founder mutation in the PEX6 gene is responsible for increased incidence of Zellweger syndrome in a French Canadian population - Levesque Sebastien; Morin Charles; Guay Simon-Pierre; Villeneuve Josee; Marquis Pascale; Yik Wing; Jiralerspong Sarn; Bouchard Luigi; Steinberg Steven; Hacia Joseph G; Dewar Ken; Braverman Nancy E (BMC, 2012)
Abstract Background Zellweger syndrome (ZS) is a peroxisome biogenesis disorder due to mutations in any one of 13 PEX genes. Increased incidence of ZS has been suspected in French-Canadians of the Saguenay-Lac-St-Jean region (SLSJ) of Quebec, but this remains unsolved. Methods We identified 5 ZS patients from SLSJ diagnosed by peroxisome dysfunction between 1990-2010 and sequenced all coding exons of known PEX genes in one patient using Next Generation Sequencing (NGS) for diagnostic confirmation. Results A homozygous mutation (c.802_815del, p.[Val207_Gln294del, Val76_Gln294del]) in PEX6 was identified and then shown in 4 other patients. Parental heterozygosity was confirmed in all. Incidence of ZS was estimated to 1 in 12,191 live births, with a carrier frequency of 1 in 55. In addition, we present data suggesting that this mutation abolishes a SF2/ASF splice enhancer binding site, resulting in the use of two alternative cryptic donor splice sites and predicted to encode an internally deleted in-frame protein. Conclusion We report increased incidence of ZS in French-Canadians of SLSJ caused by a PEX6 founder mutation. To our knowledge, this is the highest reported incidence of ZS worldwide. These findings have implications for carrier screening and support the utility of NGS for molecular confirmation of peroxisomal disorders.